Silent interests and all-pay auctions; Verborgene Interessen und "All-Pay" Auktionen - Kai Andreas Konrad (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2005)
If firms compete in all-pay auctions with complete information, silent shareholdings introduce asymmetric externalities into the all-pay auction framework. If the strongest firm owns a large share in the second strongest firm, this may make the strongest firm abstain from bidding. As a consequence, equilibrium profits of both firms may increase, but the prize may be allocated less efficiently. The reverse ownership structure is also likely to increase the profits of the firms involved in the ownership relationship but without these negative efficiency effects. – – Befinden sich Firmen im Wettkampf in All-Pay Auktionen unter vollständiger Information, so bringen stille Beteiligungen asymmetrische externe Effekte in den gesamten Auktionsrahmen. Hält die stärkste Firma einen großen Anteil an Aktien der zweitstärksten Firma, kann dies die stärkere Firma von weiteren Geboten abhalten. Als Folge vergrößern sich die Profite beider Firmen, sind jedoch weniger effizient verteilt. Das umgekehrte Eigentumsverhältnis hebt voraussichtlich die Gewinne der beteiligten Firmen an, jedoch ohne negative Effizienzauswirkungen.
Keywords: D44; L11; L41; 330; All-pay auctions; externalities; contests; silent minority shareholdings ownership structure